MODEL PEMBELAJARAN REACT UNTUK MATA PELAJARAN IPA - Hakim, Mukhammad Luqman (Edudeena : Journal of Islamic Religious Education, 2017)
Abstract: Instructional model REACT, which is a learning method that relates the lesson taught to the student's daily life, as well as trains them to work in groups to exchange their knowledge. The objective of this study is to examine the effect of contextual learning method model REACT on the science learning outcomes. This research is a part of a quasi-experimental research. The result of learning outcomes analysis of the experimental class and the control class showed that the score of tcount was 5.213 and the probability was 0.000. Because the probability score showed 0.000 less than 0.005, then H0 was rejected. So, it could be concluded that there were significant differences between the learning achievement of the control class and the experiment one. It was known tcount score was 5.213 while ttable was 1.691. Then, based on this data, the t-test was carried out in two sides with the accepted H0 between (-1.691) and (1.691). Based on these results, it can be concluded that the hypothesis (H0) which states "there is no effect on the use of contextual learning methods model REACT on the science learning achievement of fourth-grade students at SDN Malang" was rejected. It could also be concluded that there is an effect of the use of contextual learning methods model REACT on the science learning achievement of fourth-grade students. Abstrak: Model pembelajaran REACT merupakan model pembelajaran yang mengaitkan materi pelajaran dengan kehidupan sehari-hari, melatih siswa bekerjasama dalam kelompok untuk bertukar ilmu pengetahuan. Tujuan penelitian ini adalah untuk mengetahui pengaruh penggunaan metode pembelajaran kontekstual model REACT terhadap hasil belajar pada mata pelajaran IPA.Jenis penelitian ini adalah quasi experiment (eksperimen semu). Dari hasil analisis hasil belajar kelas eksperimen dan kelas kontrol diketahui bahwa nilai thitung adalah 5.213 dan probability sebesar 0.000. Karena nilai probability menunjukkan 0.000 kurang dari 0.005 maka H0 ditolak, sehingga dapat disimpulkan ada perbedaan yang signifikan antara hasil belajar kelas kontrol dan kelas eksperimen. Telah diketahui nilai thitung adalah 5.213 sedangkan nilai ttabel adalah 1.691. Berdasarkan hasil intrepretasi data, dapat disimpulkan bahwa hipotesis (H0) yang menyatakan “tidak ada pengaruh penggunaan metode pembelajaran kontekstual model REACT terhadap hasil belajar mata pelajaran IPA.